The Reconstruction of Aligarh and Santiniketan Educational Philosophy: The Creative Ijtihad of Trimurti in Developing Islamic Education in Indonesia - Kurniawan Dwi Saputra; Krismono Krismono (Universitas Darussalam Gontor, 2021)
The development of modern Islamic boarding schools‎ in Indonesia cannot be separated from the model built by the Gontor Islamic Boarding School. Gontor's education system is constructed to accommodate the continuity of Islamic religious traditions by adapting educational principles developed by exemplary institutions called sintesa. There are four specific inspirations of Gontor education: Al-Azhar in Egypt, Syanggit in Mauritania, Aligarh, and Santiniketan in India. This study aims to discuss Gontor education which is constructed from the educational philosophy of Aligarh and Santiniketan. The method used is autoethnography with the use of Giddens structuration as a theoretical framework. This study found that, in general, the influence of Aligarh and Santiniketan embodied in two aspects: symbolic and substantial. The symbolic aspect presents in the form of the nominalization of physical and non-physical infrastructure in Gontor. Substantial aspects are manifested in the modernization of the learning system and institutional governance, language skills, and the design of a holistic educational paradigm. This influence is manifested in Gontor education through a dialectical-structural step that involves the creative process of Trimurti, the founder of Gontor, to reconstruct the Aligarh and Santiniketan educational philosophies that are useful in developing and in line with Islamic education traditions. Keywords: Reconstruction, Islamic Education, Gontor, Aligarh, Santiniketan.